Prevalence of tuberculous lesion in cattle slaughtered in Mubende district, Uganda - Pakasi Nalapa, Daniel; Muwonge, Adrian; Kankya, Clovice; Olea-Popelka, Francisco (BMC veterinary research, 2017)
The aim of this study was to estimate the prevalence of gross pathology suggestive of bovine tuberculosis (TB-like lesions) and evaluate animal’s characteristics associated with the risk of having bovine TB-like lesions among cattle slaughtered in Mubende district in the Uganda cattle corridor. Method: We conducted a cross sectional study in which 1,576 slaughtered cattle in Mubende district municipal abattoir underwent post-mortem inspection between August 2013 and January 2014. The presence of bovine TBlike lesions in addition to the animal’s sex, age, breed, and sub-county of origin prior to slaughter were recorded. Associations between the presence of bovine TB-like lesions and animal’s age, sex, breed, and sub-county of origin prior to slaughter were initially analysed using a univariable approach with the chi-square test, and subsequently with a multivariable logistic regression model to assess the combined impact of these animal characteristics with the risk of having a bovine TB-like lesion. Additionally, and as a secondary objective, tissue samples were collected from all carcases that had a bovine TB-like lesion and were processed using standard Mycobacterium culture and identification methods. The culture and acid fast positive samples were tested using Capilia TB-neo® assay to identify Mycobacterium tuberculosis complex (MTC). Results: Of 1,576 carcasses inspected, 9.7% (153/1,576) had bovine TB-like lesions from which Mycobacterium spp and Mycobacterium Tuberculosis Complex (MTC) were isolated in 13 (8.4%) and 12 (7.8%) respectively. Bovine TBlike lesions were more likely to be found in females (OR = 1.49, OR 95% CI: 1.06–2.13) and in older cattle (OR = 2.5, 95% CI: 1.64–3.7). When compared to Ankole cattle, Cross breed (OR = 6.5, OR 95% CI: 3.37–12.7) and Zebu cattle (OR = 2.57, 95% CI: 1.78–3.72) had higher odds of having bovine TB-like lesions. Animals from Kasanda (OR = 2.5, 95% CI: 1.52–4.17) were more likely to have bovine TB-like lesions than cattle from Kasambya. Conclusions: The findings of study reveals that approximately one in ten slaughtered cattle presents with gross pathology suggestive of bovine TB in Mubende district in the Uganda cattle corridor district, however, we isolated MTC in only 8.4% of these bovine TB-like lesions. Therefore, there is a need to understand the cause of all the other bovine TB-like lesions in order to safe guard diagnostic integrity of meat inspection in Uganda.
Keywords: Tuberculous -like lesions; Uganda cattle corridor; Bovine tuberculosis